Association of the M1V PRKAR1A Mutation with Primary Pigmented Nodular Adrenocortical Disease in Two Large Families - Pereira, Alberto M. (The Endocrine Society, 2010)
Background: Carney complex (CNC) is a familial multiple neoplasia syndrome frequently associated with primary pigmented nodular adrenocortical disease (PPNAD), a bilateral form of micronodular adrenal hyperplasia that leads to Cushing’s syndrome (CS). Germline PRKAR1A mutations cause CNC and only rarely isolated PPNAD. Patients and Methods: PRKAR1A mutation analysis in two large families with CS and no other CNC manifestations demonstrated a M1V germline mutation; a total of 21 asymptomatic individuals were screened, and mutation carriers were evaluated for CNC. The mutation was expressed in vitro and functionally tested for its effects on protein kinase A function. Results: Presymptomatic testing identified five first-degree relatives who were M1V carriers and who were all diagnosed with subclinical, mild CS at ages ranging from 20–56 yr. There were no other signs of CNC. In a cell-free system, we detected a shorter compared with the wild-type type 1α regulatory subunit of protein kinase A (PRKAR1A) protein (43 kDa). This was not identified in cell lines from the patients or in transfection experiments in HEK293 cells that showed no detectable PRKAR1A protein from the M1V-bearing constructs. In these cells, the mutant mRNA was expressed in a 1:1 ratio. Conclusion: In two large families, the M1V PRKAR1A mutation resulted in a PPNAD-only phenotype with significant variability both in terms of age of onset and clinical severity. Expression studies showed a unique effect of this sequence change. This study has implications for genetic counseling of carriers of this PRKAR1A mutation and patients with CNC and PPNAD and for the study of PRKAR1A-related tumorigenesis.